Harnessing stem cell and lineage reprogramming technology to treat cardiac fibrosis - Ni Zeng; Wei Tang; Yanghong Wu; Hang Fan; Shuanglun Xie; Nan Cao (Cell Regeneration, 2023)
Abstract Cardiac fibrosis is a pathological response characterized by excessive deposition of fibrous connective tissue within the heart. It typically occurs following cardiac injuries or diseases. However, the lack of suitable models for disease modeling and high-throughput drug discovery has hindered the establishment of an effective treatments for cardiac fibrosis. The emergence and rapid progress of stem-cell and lineage reprogramming technology offer an unprecedented opportunity to develop an improved humanized and patient-specific model for studying cardiac fibrosis, providing a platform for screening potential drugs and synchronously elucidating the underlying molecular mechanisms. Furthermore, reprogramming cardiac fibroblasts into cardiomyocyte-like cells to reduce scar volume and induce myocardial tissue regeneration is a promising approach in treating cardiac fibrosis. In this review, we summarize the current advancements in stem cell technologies applied to study cardiac fibrosis and provide insights for future investigations into its mechanisms, drug discovery as well as therapy method.